The Development of Thinking and Reasoning. - Barrouillet, Pierre (Taylor and Francis, 2013)
Thinking and reasoning are key activities for human beings. In this book a distinguished set of contributors provides a wide readership with up-to-date scientific advances in the developmental psychology of thinking and reasoning, both at the theoretical and empirical levels. The first part of the book illustrates how modern approaches to the study of thinking and reasoning have gone beyond the Piagetian legacy: through the investigation of avenues previously not explored, and by demonstrating that young children have higher capacities than was assumed within the Piagetian trad.